2021
DOI: 10.1158/2326-6066.cir-20-0561
|View full text |Cite
|
Sign up to set email alerts
|

Modified Hypoxia-Inducible Factor Expression in CD8+ T Cells Increases Antitumor Efficacy

Abstract: Adoptive transfer of antitumor cytotoxic T cells is an emerging form of cancer immunotherapy. A key challenge to expanding the utility of adoptive cell therapies is how to enhance the survival and function of the transferred T cells. Immune-cell survival requires adaptation to different microenvironments and particularly to the hypoxic milieu of solid tumors. The hypoxia-inducible factor (HIF) transcription factors are an essential aspect of this adaptation. In this study, we undertook experiments to define st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 38 publications
3
52
0
Order By: Relevance
“…Given that HIF-2α inhibitors show encouraging results in clinical trials, in particular in the setting of treatment of VHL disease patients where long-term drug therapy is envisaged, it would be important to determine clinically whether this therapeutic intervention might also have specific inhibitory effects on anti-tumor immunity or cause more general immunosuppressive effects. Our pharmacological findings are consistent with a series of studies showing that HIF-α transcription factors are important for correct cytotoxic T cell differentiation and function in anti-tumor immunity [ 40 , 41 , 42 , 43 , 44 ] and it was recently shown that activated CD8 + liver T cells express high levels of HIF-2α and PT2385 suppressed the effector functions and survival of these cells [ 45 ]. While a phase I clinical trial of PT2385 together with nivolumab has been carried out [ 46 ], these findings also suggest that the combination of HIF-2α inhibition with immune checkpoint blockade is unlikely to be a viable therapeutic strategy.…”
Section: Resultssupporting
confidence: 91%
“…Given that HIF-2α inhibitors show encouraging results in clinical trials, in particular in the setting of treatment of VHL disease patients where long-term drug therapy is envisaged, it would be important to determine clinically whether this therapeutic intervention might also have specific inhibitory effects on anti-tumor immunity or cause more general immunosuppressive effects. Our pharmacological findings are consistent with a series of studies showing that HIF-α transcription factors are important for correct cytotoxic T cell differentiation and function in anti-tumor immunity [ 40 , 41 , 42 , 43 , 44 ] and it was recently shown that activated CD8 + liver T cells express high levels of HIF-2α and PT2385 suppressed the effector functions and survival of these cells [ 45 ]. While a phase I clinical trial of PT2385 together with nivolumab has been carried out [ 46 ], these findings also suggest that the combination of HIF-2α inhibition with immune checkpoint blockade is unlikely to be a viable therapeutic strategy.…”
Section: Resultssupporting
confidence: 91%
“…Interestingly, they also reported that HypoxiCAR T-cells were not excluded from HIF-1-stabilized regions of the tumor (Figure 3). differentiation, and improving the rejection of primary and metastatic melanoma tumors [431]. [432].…”
Section: Perspectives On the Interplay Between Hypoxia And Immunotherapiesmentioning
confidence: 99%
“…Deletion of the transcription factor Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2) impaired the enhancing effect of hypoxia. Another study showed that HIF-2α, but not HIF-1α, drove broad transcriptional changes in CD8 + T-cells, resulting in increased cytotoxic differentiation and cytolytic function against tumors [431]. Moreover, a HIF-2 form that is insensitive to FIH was delivered with anti-CD19 CAR T-cells.…”
Section: Perspectives On the Interplay Between Hypoxia And Immunotherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in a mouse melanoma model HIF-1α -/- CD8 + T cells show decreased expression of soluble factors including TNFα, IFNγ and granzyme B and tumor infiltration under hypoxia correlating with increased tumor growth ( 17 ). Moreover, ectopic expression of HIF-2α improved CD8+ T cell antitumor activity, revealing HIF-1α -/- CD8 + T cells as a potential adoptive cell therapy tool overcoming the harmful hypoxic TME ( 46 ). HIF-1α was also reported to enhance murine Treg differentiation ( 47 ).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%